EL RECUERDO DE LA MARCA EN LA EXPOSICIÓN DE IMÁGENES AFECTIVAS - Laura Estela Fischer de la Vega; Oscar Zamora Arevalo (European Scientific Journal, ESJ, 2013)
In graphic communication, persuasion is through the values of a brand concept, which involves the combination of a sharp image with the stimulation of human emotions. The images themselves generate an emotion.The model bioinformational International Affective Picture System (IAPS), analyzed, normalized and standardized emotional over 1200 images on a psychological context. However, in marketing these images have not been studied, which are the most suitable images to be associated with the product and so choose suitable for the product is perceived by the target market.This research seeks to measure the memory of the brand exposure to affective pictures as a slide show presented in the IAPS (International Affective Picture System), through an experimental study based on the model of Peter Lang bioinformational where 60 images were analyzed by the International Affective Picture System (IAPs) highly emotional load: 20 positive and 20 negative images, additionally, 20 images were analyzed emotional uncharged or neutral, to each of which are inserted and positioned a recognized brand on the market, taken from the list of BrandZ top 100 of Millward Brown, 2010 to be evaluated by 300 students of the 5th semester BA from the School of Accounting and Administration of the National University of Mexico, using a sheet assessment to write down the ten images that recalled and what was the brand image showing.With the result we obtained data that may be useful in the field of marketing for the development of graphic communication strategies that will allow entrepreneurs have a greater impact on attention, recall and purchase in the design of visual communication campaigns.